Health expenditures for cases of pleural mesothelioma - Zocchetti, Carlo (La Medicina del Lavoro, 2015)
Through the study of 65 cases of probable pleural mesothelioma currently under discussion in 4 criminal trials in the Lombardy Region, who died between 2002 and 2015, this study aimed to provide economical information regarding the health expenditures sustained by the Regional Health Service (RHS) for providing hospitalization, outpatient services and drugs to such patients. Health information regarding the services provided for the cases under study were electronically retrieved from the RHS information system. For each pleural mesothelioma case the costs (on average) were about 67,000 euros, 37,000 of which were spent after the date of diagnosis. Drugs formed the largest part of health expenditure (about 37,000 euros per person). Per capita expenditures showed a peak near (before and after) the date of diagnosis, rising when approaching the date of death and with increasing age of the patient, and did not vary with survival time. This information, reported for the first time in detail in this paper, will be useful for out-of-court agreements and for setting up reimbursement schemes, and describe per capita expenditures which are higher than estimations proposed in recent criminal trials in Italy and to those reported in the international literature.